Strategy of Implementing Blue Economy Policy in Developing Marine Tourism - Roem, Muhammad; Ibrahim, Muhammad Akmal; Nara, Nurdin; Abdullah, Muhammad Tang; Iskandar, Didik (Journal La Bisecoman, 2025)
The researchers evaluate how Blue Economy principles apply during the development of marine tourism activities in Makassar City Indonesia. This study uses qualitative case methods alongside Mintzberg’s strategic dimensions: plan, pattern, position, perspective, and play for examining marine tourism governance over institutions and between communities and policy structures. Interviews with government officials alongside community leaders and tourism stakeholders together with field observation and document evaluation served as the data collection methods. Data shows that institutional bodies have started adopting Blue Economy principles yet its practical implementation continues to remain scattered. The absence of legal norms and insufficient regulatory framework exists while stakeholders play unclear roles and environment sustainability takes a backseat priority to quantitative performance targets. The responsible development practices initiated by communities and NGOs create a foundation linking with Blue Economy concepts even though their work remains informal and separate from official programs. The analysis exposes major strategic differences between actors together with a need for tactical fixes because organized plans are missing.